2018
DOI: 10.1101/317248
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Knowledge, attitudes and awareness of the human papillomavirus among health professionals in New Zealand

Abstract: BackgroundHuman papillomavirus (HPV) is a common sexually transmitted infection that is implicated in 99.7% of cervical cancers and several other cancers that affect both men and women. Despite the role that HPV plays in an estimated 5% of all cancers and the evolving role of HPV vaccination and testing in protecting the public against these cancers, preliminary research in New Zealand health care professionals suggest knowledge about HPV may not be sufficient.MethodsA total of 230 practice nurses, smear taker… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
5
2
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 10 publications
1
5
2
1
Order By: Relevance
“…A similar study showed adequate awareness about the virus among healthcare workers in New Zealand. However, significant gaps in knowledge were still noted 29…”
Section: Discussionmentioning
confidence: 99%
“…A similar study showed adequate awareness about the virus among healthcare workers in New Zealand. However, significant gaps in knowledge were still noted 29…”
Section: Discussionmentioning
confidence: 99%
“…17 In addition to not being easily accessible, concerns about the association with sexually transmitted infections (STIs), promiscuity, adverse effects, low recommendation of the vaccine by professionals, costs and lack of knowledge have led to the low rate of HPV vaccination in the target population. 13,16 Increased awareness had a positive effect on the intention to take the vaccine, and women were more likely to have a positive attitude toward vaccination. 9,15 Likewise, for Monteiro et al, 10 more women were interested in taking the vaccine and, in general, higher-education students were more interested in the vaccination.…”
Section: Discussionmentioning
confidence: 99%
“…3 In our study, 76% of the participants were aware of the causal nature of HPV in cervical carcinogenesis. This question has been examined by several authors 5,9,[14][15][16] among students from a variety of courses, with the rate of correct answers ranging from 48 to 98%. Regarding the knowledge that HPV is related to other cancers, the proportion of correct answers did not exceed 40% for any type of cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, various factors may influence the level of knowledge of health professionals. In half of the studies included in the systematic review, it appears that the level of awareness of a high risk of oncogenic HPV types was observed to be significantly differentiated between health professionals of different specialties [18][19][20][21][22]. More specifically, general practitioners, gynecologists, pediatricians, and workers in obstetric nursing units (midwives, nurses) showed a higher awareness of high-risk HPV genotypes than the rest of the paramedical staff, whose relative rates of knowledge and awareness were too low.…”
Section: Discussionmentioning
confidence: 99%